Moral values found in the album thankyou allah by maher zein - Fitri Windayanti; Tahrun Tahrun; Mulyadi Mulyadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aimed to find out the moral values in the album thank you Allah by Maher Zein and the theoretical implication for teaching songs and ELT. The research method used in this study was descriptive qualitative method. The sources of data were ten song lyrics from Maher Zein album. Method of collecting the data was triangulation: lyrics, interview, and book review. The data of this study were analyzed through: listening the songs, reading ten lyrics from the album, and analyzing the moral values by underlining, defining, classifying, reanalysing, and coding. The research found ten moral values in the album were: love and affection, believe, thankfully, forgiveness, loyalty, togetherness, honesty, bravery, courage and struggle. By analyzing the moral values, hopefully it could build the good character for us and finally we could give an inspiration to others. For the theoretical implication, it could be concluded that moral values could be taught through songs